Ungulate management in European national parks: Why a more integrated European policy is needed. (15th April 2020) - van Beeck Calkoen, Suzanne T.S.; Mühlbauer, Lisa; Andrén, Henrik; Apollonio, Marco; Balčiauskas, Linas; Belotti, Elisa; Carranza, Juan; Cottam, Jamie; Filli, Flurin; Gatiso, Tsegaye T.; Hetherington, David; Karamanlidis, Alexandros A.; et al.
Abstract: 1. Primary objectives of national parks usually include both, the protection of natural processes and species conservation. When these objectives conflict, as occurs because of the cascading effects of large mammals (i.e., ungulates and large carnivores) on lower trophic levels, park managers have to decide upon the appropriate management while considering various local circumstances. 2. To analyse if ungulate management strategies are in accordance with the objectives defined for protected areas, we assessed the current status of ungulate management across European national parks using the naturalness concept and identified the variables that influence the management. 3. We collected data on ungulate management from 209 European national parks in 29 countries by means of a large-scale questionnaire survey. Ungulate management in the parks was compared by creating two naturalness scores. The first score reflects ungulate and large carnivore species compositions, and the second evaluates human intervention on ungulate populations. We then tested whether the two naturalness score categories are influenced by the management objectives, park size, years since establishment, percentage of government-owned land, and human impact on the environment (human influence index) using two generalized additive mixed models. 4. In 67.9% of the national parks, wildlife is regulated by culling (40.2%) or hunting (10.5%) or both (17.2%). Artificial feeding occurred in 81.3% of the national parks and only 28.5% of the national parks had a non-intervention zone covering at least 75% of the area. Furthermore, ungulate management differed greatly among the different countries, likely because of differences in hunting traditions and cultural and political backgrounds. Ungulate management was also influenced by park size, human impact on the landscape, and national park objectives, but after removing these variables from the full model the reduced models only showed a small change in the deviance explained. In areas with higher anthropogenic pressure, wildlife diversity tended to be lower and a higher number of domesticated species tended to be present. Human intervention (culling and artificial feeding) was lower in smaller national parks and when park objectives followed those set by the International Union for the Conservation of Nature (IUCN). 5. Our study shows that many European national parks do not fulfil the aims of protected area management as set by IUCN guidelines. In contrast to the USA and Canada, Europe currently has no common ungulate management policy within national parks. This lack of a common policy together with differences in species composition, hunting traditions, and cultural or political context has led to differences in ungulate management among European countries. To fulfil the aims and objectives of national parks and to develop ungulate management strategies further, we highlight the importance of creating a more integrated European ungulate management policy to meet the aims of national parks. Highlights: We used the naturalness score to assess ungulate management in protected areas. Ungulate management in national parks varied greatly among European countries. Ungulate management reflects differences in legislation, policy and traditions. An integrated European ungulate management framework for national parks is needed.